Quantitative Estimation of Urate Transport in Nephrons in Relation to Urinary Excretion Employing Benzbromarone-Loading Urate Clearance Tests in Cases of Hyperuricemia - Toru Nakamura (Nephron Extra, 2011)
Background: A four-component system for urate transport in nephrons has been proposed and widely investigated by various investigators studying the mechanisms underlying urinary urate excretion. However, quantitative determinations of urate transport have not been clearly elucidated yet. Methods: The equation Cua = {Ccr(1 – R1) + TSR}(1 – R2) was designed to approximate mathematically urate transport in nephrons, where R1 = urate reabsorption ratio; R2 = urate postsecretory reabsorption ratio; TSR = tubular secretion rate; Cua = urate clearance, and Ccr = creatinine clearance . To investigate relationships between the three unknown variables (R1, R2, and TSR), this equation was expressed as contour lines of one unknown on a graph of the other two unknowns. Points at regular intervals on each contour line for the equation were projected onto a coordinate axis and the high-density regions corresponding to high-density intervals of a coordinate were investigated for three graph types. For benzbromarone (BBR)-loading Cua tests, Cua was determined before and after oral administration of 100 mg of BBR and CuaBBR(∞) was calculated from the ratio of CuaBBR(100)/Cua. Results: Before BBR administration, points satisfying the equation on the contour line for R1 = 0.99 were highly dense in the region R2 = 0.87–0.92 on all three graphs, corresponding to a TSR of 40–60 ml/min in hyperuricemia cases (HU). After BBR administration, the dense region was shifted in the direction of reductions in both R1 and R2, but TSR was unchanged. Under the condition that R1 = 1 and R2 = 0, urate tubular secretion (UTS) was considered equivalent to calculated urinary urate excretion (Uex) in a model of intratubular urate flow with excess BBR; CuaBBR(∞) = TSR was deduced from the equation at R1 = 1 and R2 = 0. In addition, TSR of the point under the condition that R1 = 1 and R2 = 0 on the graph agreed with TSR for the dense region at excess BBR. TSR was thus considered approximately equivalent to CuaBBR(∞), which could be determined from a BBR-loading Cua test. Approximate values for urate glomerular filtration, urate reabsorption, UTS, urate postsecretory reabsorption (UR2), and Uex were calculated as 9,610; 9,510; 4,490; 4,150, and 440 µg/min for HU and 6,890; 6,820; 4,060; 3,610, and 520 µg/min for normal controls (NC), respectively. The most marked change in HU was the decrease in TSR (32.0%) compared to that in NC, but UTS did not decrease. Calculated intratubular urate contents were reduced more by higher UR2 in HU than in NC. This enhanced difference resulted in a 15.4% decrease in Uex for HU. Conclusion: Increased UR2 may represent the main cause of urate underexcretion in HU.